Research on smart city construction in the context of public culture - Yuhang Zhang; Jiaji Gao (Telematics and Informatics Reports)
This paper aims to explore smart city construction in the context of public culture in order to understand the new opportunities and challenges of urban development in the context of the digital era. The emergence of digital media such as interactive technology and virtual reality has changed the service mode of traditional public culture, providing more diversified channels for the public to express their opinions and participate in urban and social governance. However, the social value of humanistic factors such as public culture has been seriously neglected in the construction of smart cities, and there is an urgent need for its value-orientation to put the overly technology-focused enterprise-led smart city construction back on the right path. This paper discusses the development status of smart cities, the advantages and shortcomings of smart cities, and the importance of public culture. In this paper, we analyse the current development status, diverse characteristics, advantages and shortcomings of Chinese smart cities in the context of four cities, namely Beijing, Shanghai, Shenzhen and Hangzhou, and point out the lack of public culture construction in Chinese smart cities. Further, the research delineates five key values of public culture in smart city development and constructs a comprehensive evaluation framework comprising 31 indicators across six dimensions: supply, participation, innovation, fairness, suitability, and richness. Based on this framework, six recommendations are proposed for the development of public cultural initiatives in smart cities to enhance their positive impact on urban development, and to provide a new perspective for promoting the construction of a better and more warm-hearted smart city.